JUMPA Vol. 4 No. 1, Feb 2017 PENGARUH KEPRIBADIAN DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN PT. POS INDONESIA (PERSERO) WILAYAH BEKASI: PENGARUH KEPRIBADIAN DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN PT. POS INDONESIA (PERSERO) WILAYAH BEKASI - Lies Kantinia Rohma Sekolah Tinggi Ilmu Ekonomi Y.A.I; Alex Zami Sekolah Tinggi Ilmu Ekonomi Y.A.I (Jurnal Manajemen dan Perbankan (JUMPA), 2017)
In this research is studied the influence of organizational culture on personality and Organizational Citizenship Behavior(OCB) to theemployees of PT. POS INDONESIA (Persero) BEKASI AREA. The independent variablesin this studyis the personality and culture of the organization, while the dependent variable Organizational Citizenship Behavior (OCB). This study aimsto determine the effectof personality and organizational culture both partial and together the Organizational Citizenship Behavior (OCB) to theemployees of PT. POS INDONESIA(Persero) BEKASI AREA. The method usedin this research isdescriptive and verification methods. Givena population of 60 people, the method use disproportional random sampling. Methods of data analysis using SPSS software Ver. 21:00. The results of this study proveeitherpartially or jointlypersonality and organizational culturepositive and significant impacton Organizatinal Citizenship Behavior, where Fhitung9.295>Ftabel3.16 and a significance levelof 0.000<0.05 so the research hypothesis H1, H2 and H3 accepted,it is also supported by theRsquare valueof 24.6%. It shows the contribution of personality and influence of organizational culture on Organization Citizenship Behaviorat 24.6%.